A Commercial Anti-TIF1γ ELISA Is Superior to Line and Dot Blot and Should Be Considered as Part of Routine Myositis-Specific Antibody Testing - Mulhearn, Ben; Li, Danyang; McMorrow, Fionnuala; Lu, Hui; McHugh, Neil J.; Tansley, Sarah L. (Frontiers in Immunology, 2022)
Objectives: Anti-TIF1γ is an important autoantibody in the diagnosis of cancer-associated dermatomyositis and the most common autoantibody in juvenile onset dermatomyositis. Its reliable detection is important to instigate further investigations into underlying malignancy in adults. We previously showed that commercial assays using line and dot blots do not reliably detect anti-TIF1γ. We aimed to test a new commercial ELISA and compare with previously obtained protein immunoprecipitation. Methods: Radio-labelled immunoprecipitation had previously been used to determine the autoantibody status of patients with immune-mediated inflammatory myopathies and several healthy controls. ELISA was undertaken on healthy control and anti-TIF1γ sera and compared to previous immunoprecipitation data. Results: A total of 110 serum samples were analysed: 42 myositis patients with anti- TIF1γ and 68 autoantibody negative healthy control sera. Anti-TIF1γ was detected by ELISA in 41 out of 42 of the anti-TIF1γ-positive samples by immunoprecipitation, and in none of the healthy controls, giving a sensitivity of 97.6% and specificity of 100%. The false negative rate was 2%. Conclusion: ELISA is an affordable and time-efficient method which is accurate in detecting anti-TIF1γ.